Análisis espacial de lanzamientos en baloncesto; el caso de L.A. Lakers - Lopez, F. A.; Martinez, J. A.; Ruiz, M. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2013)
The importance of quantitative analysis in sports using objective data (such as game statistics), has been had prominent in recent years. In this paper we have shown an application of spatial statistics to understand more thoroughly the game of basketball. This methodology has been rarely used in sports research, specifically in basketball. We have depicted how a spatial clustering technique, such as the Kulldroff test, which is widely employed in epidemiology, can be applied to analyze basketball data. This test detects low and high incidence clusters of shots, and therefore it better characterizes the game of teams and individual players. In addition, we have also used a test based on entropy, the V-test, which serves to statistically compare shooting maps. We illustrate the interesting contribution of this methodological perspective in the case of the analysis of the Lakers` performance, showing the transformation of this team from a medium-level NBA franchise into a champion team, because of, among other factors, the incorporation of two key players in the 2007-08 season: Pau Gasol and Derek Fisher.